Digital Transformation and COVID-19: The Case of Greece - Achillefs Vratimos (European Scientific Journal, ESJ, 2023)
The impact of the COVID-19 pandemic has caused significant problems to different public sector functions worldwide. This extends further than just public health. To protect citizens and keep services functional, the digital transformation of the public sector was selected by many countries as the most reliable solution (a policy with the goal of servicing citizens on-time and efficiently). Greece lagged significantly behind the European average in terms of digital governance. A different policy aiming at the development of digital governance applications was adopted in mid-2019. The scope of this paper is to examine how the pandemic (since the first months of 2020) has contributed to the impressive acceleration of the digital transformation processes of the central administration. This paper presents in detail the innovative applications implemented by Greece in the context of combating and limiting the effects of the COVID-19 pandemic as supported by statistics that reflect the spread of these applications. In summary, we see that through digital governance applications, the implementation of the lockdown was controlled, and, at the same time, many procedures were made digital. As a result, there would be no need for physical presence in public services for their processing. Examples of that include electronic prescribing, continuous monitoring of COVID cases, and vaccination appointment scheduling for the defense against COVID-19.This, therefore, became possible because of this digitalization approach. The success of this approach is evident in the National Theater’s performances, as well as many of the country's museums contents, which were converted and transmitted in digital format. Volunteerism was also promoted to strengthen hospitals and other units. Such state measures to deal with the COVID-19 pandemic and its consequences demonstrated the importance of leveraging the digital resources of public administration (networks, connectivity and interaction of digital skills) and how effectively Greece grasped the opportunity to accelerate the implementation of a lot of digital transformations towards digital governance.